Wisata Minat Khusus : Objek Wisata Pendakian di Gunung Marapi (2016-2022) - Resandi, Mario; Najmi, Najmi (Jurusan Sejarah FIS UNP, 2024)
This research is a historical study that discusses the management of the Mount Marapi climbing tourist attraction from 2016-2022. The aim of this research is to (1) Desribe the management of the climbing tourist attraction on the Koto Baru route in the Mount Marapi Nature Tourism Park by Pokdarwis Koto Baru from 2016-2022 (2) Describe the management of the climbing tourist attraction on the mount Marapi by the West Sumatra Natural Resources Conversation Center. This research uses a historical method with the following steps: Heuristics or data collection, after the data is obtained then the source is criticized using external criticism and internal criticism then continues with interpretation. The final stage is writing history or historiography so that this research can be completed. The result of this research show that there are differences in the management of tourist attractions by each management between the Koto Baru religious tourism awareness group and the West Sumatra Natural Resources Conservation Center, which greatly influences the condition of special interest tourist attractions in terms of mountain climbing.